Is there a relationship between preoperative cytological diagnosis and evolution in patients with differentiated thyroid carcinoma? A retrospective study - Colenci, Renato [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Soares, Carlos Segundo Paiva [UNESP]; Oliveira, Cristiano Claudino de [UNESP]; Marques, Mariângela Esther de Alencar [UNESP]; Tagliarini, José Vicente [UNESP]; Mazeto, Gláucia Maria Ferreira da Silva [UNESP] (Archives of Endocrinology and Metabolism, 2022)
Objective: Cytological analysis and Bethesda classification of thyroid nodules is the standard method of diagnosing differentiated thyroid carcinoma (DTC). However, even for nodules with a non-malignant cytological diagnosis, there is a not insignificant risk of cancer. There are doubts whether this lack of certainty would influence patient prognosis. Our aim was to compare patients with DTC, classified according to the preoperative cytological diagnosis, regarding their evolution. Subjects and methods: A retrospective study was carried out with 108 DTC patients submitted to total thyroidectomy (TT) between 2009 and 2015, divided into three groups according to preoperative cytological diagnosis (Bethesda classification): classes I/II, III/IV, and V/VI. Groups were compared for evolution considering response to treatment at last evaluation as well as time disease free. Statistical analysis used ANOVA, chi squared, and Kaplan-Meier curves with p<0.05 considered significant. Results: Groups differed for time between nodule puncture and TT [in months; V/VI (2.35 ± 2.48) < III/IV (7.32 ± 6.34) < I/II (13.36 ± 8.9); p < 0.0001]. There was no significant difference between groups for evolution at final evaluation (disease free status; classes I/II: 71.4%; classes III/IV: 60%; classes V/VI: 66.6%; p = 0.7433), as well as time disease free (in months; classes I/II: 34.57 ± 25.82; classes III/IV: 38.04 ± 26.66; classes V/VI: 30.84 ± 26.34; p = 0.3841). Conclusions: DTC patients classified according to preoperative cytological diagnosis did not differ for evolution. Although patients with non-malignant cytological diagnoses were submitted to TT later, this did not affect the evolution of the cases.
Keywords: cytology; Fine-needle biopsy; prognosis; thyroid neoplasms